Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Discover a wealth of knowledge from experts across different disciplines on our comprehensive Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Answer:
log4x+log4(x-6)=2
place under single log using multiplication rule
log4(x(x-6))=2
convert to exponential form:(base(4) raised to log of number(2)=number(x(x-6)
4^2=x(x-6)
16=x^2-6x
x^2-6x-16=0
(x-8)(x+2)=0
x=8
or
x=-2 (reject, x>0)
Step-by-step explanation:
Answer:
[tex]\sf x=2, \ x = -8[/tex]
solving steps:
[tex]\hookrightarrow \sf log_4 x+log_4 (x+6)=2[/tex]
[tex]\hookrightarrow \sf log_4 (x(x+6))=log_4 (16)[/tex]
[tex]\hookrightarrow \sf log_4 (x^2+6x)=log_4 (16)[/tex]
[tex]\hookrightarrow \sf x^2+6x=16[/tex]
[tex]\hookrightarrow \sf x^2+6x-16=0[/tex]
[tex]\hookrightarrow \sf x^2+8x-2x-16=0[/tex]
[tex]\hookrightarrow \sf x(x+8)-2(x+8)=0[/tex]
[tex]\hookrightarrow \sf (x-2)(x+8)=0[/tex]
[tex]\hookrightarrow \sf x=2, \ x = -8[/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.